Effects of Crude Oil on Geotechnical Specification of Sandy Soils. Issue 1 (2nd January 2021) - Ostovar, Mojtaba; Ghiassi, Reza; Mehdizadeh, Mohammad Javad; Shariatmadari, Nader
ABSTRACT: Soil contamination is one of the common and controversial environmental issues all over the world. Soil pollution through extraction, transfer, and petrochemical activities of petroleum products causes both environmental issues and geotechnical problems. Such pollution can reduce soil bearing capacity and can change soil permeability. In this paper, a series of geotechnical tests have been performed to investigate this problem, including direct shear test, permeability test, compaction test, X-ray diffraction, and Atterberg limits. Sandy soil samples were mixed with different percentages of crude oil and tested. The results from direct shear tests indicate a decrease in the internal friction angle of the samples due to increasing oil contamination level about 4 to 12 degrees. Also, the results show that oil contamination reduces cohesion in the clayey sand and increases cohesion in the other samples about 5 to 15 kPa. The effect of evaporation of some oil compounds on shear strength has been also tested on 16% contaminated samples and the results have been discussed. The results of permeability tests show that with the increase in the soil contamination up to 16%, the permeability coefficient of clayey sand samples increases about 50 times, while it does not vary too much for poorly-graded sand, well-graded sand, and silty sand.